Understanding of Nature of Science (NOS) among Pre-service Teachers and Teacher Educators - Singhal, Mamta (JOURNAL OF INDIAN EDUCATION, 2017)
The place of Nature of Science (NOS) in science curricula has been emphasised worldwide. NOS is considered an important component of scientific literacy. Science educators and researchers have given various arguments to support the inclusion of Nature of Science as an important component in science education. The policy frameworks and the researches in the field of science education have indicated the need to conduct systematic research on Nature of Science at all levels—school, college and teacher education—and disseminate the findings widely at the national level. In India, the concerns about NOS are being raised at the level of curriculum reforms. Position paper (1.1) on Teaching of Science, NCERT (2006) advocated scientific literacy; distinction between science and technology; relationship of science, technology and society; process of science; and understanding the historical and developmental perspectives of science at all levels of school education. These goals cannot be accomplished without an emphasis on Nature of Science. Despite these recommendations, the traditional pedagogical approach, lack of resources and lack of support to the teachers lead to no significant changes in the practical scenario in terms of inclusion of NOS. The teacher education programmes have also recognised the need of developing an understanding of NOS among prospective teachers and hence included some units on Nature of Science in their syllabi. However, most teacher educators and prospective teachers do not seem to give enough importance to this. The study explored the understanding of NOS among pre-service teachers and teacher educators of Bachelor of Education (B.Ed.) programme of three universities in Delhi.